2013
DOI: 10.1002/jbmr.1850
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals FAM20c mutations associated with fibroblast growth factor 23–related hypophosphatemia, dental anomalies, and ectopic calcification

Abstract: Fibroblast growth factor 23 (FGF23) plays a crucial role in renal phosphate regulation, exemplified by the causal role of PHEX and DMP1 mutations in X-linked hypophosphatemic rickets and autosomal recessive rickets type 1, respectively. Using whole exome sequencing we identified compound heterozygous mutations in family with sequence similarity 20, member C (FAM20C) in two siblings referred for hypophosphatemia and severe dental demineralization disease. FAM20C mutations were not found in other undiagnosed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 55 publications
3
137
1
Order By: Relevance
“…Mutation to a Trp would severely interfere with packing of the C-lobe and disrupt protein integrity. Recently, Rafaelsen et al (18) identified compound heterozygous mutations in FAM20C in siblings with clinical presentation of dental abnormalities, ectopic calcifications, and fibroblast growth factor 23-related hypophosphatemia. A novel missense mutation, Thr268Met, was reported in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation to a Trp would severely interfere with packing of the C-lobe and disrupt protein integrity. Recently, Rafaelsen et al (18) identified compound heterozygous mutations in FAM20C in siblings with clinical presentation of dental abnormalities, ectopic calcifications, and fibroblast growth factor 23-related hypophosphatemia. A novel missense mutation, Thr268Met, was reported in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mutations in FAM20C cause Raine syndrome, a deadly osteosclerotic bone dysplasia characterized by generalized osteosclerosis, ectopic calcifications, and characteristic facial features (14-16). Most individuals with Raine syndrome die within a few weeks after birth; however, nonlethal cases with dental abnormalities and clinical features of hypophosphatemia have been reported (17,18). Loss of Fam20C in mice also results in severe bone and tooth anomalies, as well as hypophosphatemia (19)(20)(21).…”
mentioning
confidence: 99%
“…Contemporaneous with our finding that Fam20C is a protein kinase, Wang et al (13) characterized Fam20C KO mice and demonstrated that these animals develop hypophosphatemic rickets as a result of elevated serum intact, bioactive FGF23. Furthermore, a recent report identified compound heterozygous mutations in FAM20C in two siblings referred for hypophosphatemia and severe dental demineralization disease (12). Biochemical analysis of the patients' sera identified elevated intact FGF23.…”
Section: Fgf23mentioning
confidence: 94%
“…Subsequently, mutations in the FAM20C gene were found to be responsible for this disorder (10), and recent reports suggest a broader phenotypic spectrum for individuals with FAM20C mutations because some patients survive infancy (12,34). Notably, Rafaelsen et al (12) identified a novel missense mutation in Fam20C that substituted Thr 268 with a Met in two compound heterozygous brothers who had elevated serum intact FGF23 and hypophosphatemia.…”
Section: Incomplete Inhibition Of Fgf23 O-glycosylation By Fam20c T268mmentioning
confidence: 99%
See 1 more Smart Citation